C/MIC > 4: A Potential Instrument to Predict the Efficacy of Meropenem - Yichang Zhao; Chenlin Xiao; Jingjing Hou; Jiamin Wu; Yiwen Xiao; Bikui Zhang; Indy Sandaradura; Hong Luo; Jinhua Li; Miao Yan (MDPI AG, 2022)
This prospective study aimed to explore the determinants of meropenem trough concentration (Ctrough) in patients with bacterial pneumonia and to investigate the association between its concentration and efficacy. From January 2019 to December 2019, patients with pulmonary infections were prospectively enrolled from the intensive care unit. Factors affecting the meropenem trough concentration were analyzed, and a multiple linear regression model was constructed. Logistic regression analyses were used to investigate the relationship between Ctrough and clinical efficacy. A total of 64 patients were enrolled, in whom 210 meropenem concentrations were measured. Of the total, 60.9% (39/64) were considered clinically successful after treatment. Ctrough may increase with increased blood urea nitrogen, albumin, and concomitant antifungal use. By contrast, concentration may decrease with increased endogenous creatinine clearance rate. Six variables, including Ctrough/minimum inhibitory concentration (MIC) > 4, were associated with the efficacy of meropenem. There was an independent correlation between Ctrough/MIC > 4 and efficacy after fully adjusting for confounding factors. Based upon renal function indexes, it is possible to predict changes in meropenem concentration and adjust the dosage precisely and individually. Ctrough/MIC > 4 is a potential instrument to predict successful treatment with meropenem.